Impact Of Covid-19 On Understanding Organic Chemistry for New Students in Iraqi Universities - Zahraa Ali Nashoor Alnawas (Genius Journals, 2022)
COVID-19 has besieged academic institutions worldwide. As countries closed their international borders and imposed lockdowns, tertiary-education institutions have had to move quickly toward online offering to maintain continuation of teaching and learning. Faculty members have encountered enormous obstacles in replacing traditional face-toface lectures with alternate means of instruction and assessment. This shift appears to have been relatively easy for countries that invested in education and approached elearning strategically prior to the crisis. Countries that have not created a strategic approach to e-learning cannot provide the necessary assistance, and those that have witnessed lower development in higher education in general have faced considerable challenges. In this study, we show how chemistry instructors dealt with and overcame the challenges of teaching a freshman organic course at a period of stringent safety regulations. We discuss how the assessment mechanisms in our course have changed, as well as the effects of these modifications on our students' academic performance and teacher feedback ratings
Keywords: COVID-19 Pandemic; Organic chemistry; Students; Iraqi universities